Medicines adherence in children - Aldosari, Mohammed (2021)
Poor medicines adherence in children is one of the common problems in the health care system. Knowing the medicines adherence rate in individual children is important to understand the consequences of non-adherence. Different factors can contribute to poor adherence such as forgetting, lack of understanding about the treatment or disease, age of child, socioeconomic status, medicines schedule and taste. Strategies that target these factors may improve medicines adherence. This research explores methods of measuring medicines adherence and the barriers and facilitators to medicines adherence in children with diverse diseases.